PENINGKATAN SELF-EFFICACY SISWA MELALUI STRATEGI PERSUASI VERBAL PADA PROGRAM EKSTRAKURIKULER KEAGAMAAN DI MA AL-BAIRUNY SAMBONG DUKUH JOMBANG - Ahmad Fatkhurrozak; Rofiatul Hosna; Asriana Kibtiyah (Kurikula : Jurnal Pendidikan, 2024)
This study examined self-efficacy among students at MA Al-Bairuny Sambong Dukuh Jombang and explored ways to enhance it through verbal persuasion strategies in religious extracurricular programs. Data was collected through observation, interviews, and documentation. The findings revealed an increase in students' self-confidence and courage, along with the supporting role of religious extracurricular teachers. However, inhibiting factors included inadequate facilities, teacher absence, and individual differences among students. Overall, the study emphasizes the importance of self-efficacy and provides insights into its promotion in religious extracurricular activities.